The role of extra-familial factors in adolescence for the association between out-of-home care and adult psychiatric disorders-A birth cohort study. - Lisa Bornscheuer; Evelina Landstedt; Ylva B Almquist (PLoS ONE)
Background Psychiatric disorders are a substantial public health concern, and childhood adversity a well-known risk factor for it. Investigating gender differences in vulnerability and resilience processes following out-of-home care (OHC) as proxy for childhood adversity can help map opportunities for the prevention of psychiatric disorders. Methods We followed a large birth cohort for psychiatric disorders (anxiety, depression, and self-harm, and substance misuse) between age 25-62 years, comparing individuals with and without OHC experience. We investigated different extra-familial risk and resources factors following OHC via gender-stratified mediation and moderation analyses to approximate risk accumulation (vulnerability processes) and buffers of risk (resilience processes). Results OHC is prospectively associated with psychiatric disorders in adulthood. Lower school grades, delinquency, and early parenthood are mediators of the association, with the exception of education in girls in relation to anxiety, depression, and self-harm, and early parenthood in boys in relation to substance misuse. Number of best friends moderates OHC experience in boys, and there is a trend for higher educational achievement to also act as buffer, even though this trend was not statistically significant. Leisure time activities did not act as buffer. Conclusion Vulnerability and resilience processes after childhood adversity are gendered: Risk accumulation runs via delinquency and poorer educational outcomes in boys more than in girls, while early parenthood is a more dominant risk factor in girls. Having more best friends and higher grades may act as buffer, especially in boys.